Análisis de las estrategias para el aprendizaje del idioma inglés aplicadas por los estudiantes del séptimo semestre de la Carrera de Comunicación Social - Mosquera Gonzáles, Yuliana Solange (2020)
The realization of the present case study has as its main objective to determine, through the execution of interviews what are the language learning strategies (cognitive, cognitive, affective and social goals) that students and teachers use to improve the process of learning English In addition to proposing a theoretical foundation that provides knowledge about the importance of learning strategies for the achievement of personal and professional goals, the importance of having an ideal environment to improve the teaching process will be analyzed will the help of data collection techiques such as the interview and the survey. The data specified the need to use better learning strategies such as the design of a computer application to support the teacher resulting in more meaningful learning in terms of appropriation of new content in the target language. The results show that constant training in learning strategies develops the ability to trace goals, monitor and evaluate learning (cognitive meta strategies), help learn new structures (cognitive strategies), control anxiety (affective strategies) and seek interaction in the target language (social strategies); all this to help improve students' language skills in learning the target language.